NASIONALISASI PERUSAHAAN PENANAMAN MODAL ASING DI INDONESIA - I Gusti Agung Mas Triwulandari; I Nyoman Budiana (Jurnal Analisis Hukum, 2018)
The purpose of this study is to understand the basis of the government action to nationalize foreign investment companies and legal protection of investors as a result of these nationalization actions. The research method used is normative juridical or library research related to normative substance of law, to find truth based on logic of science regarded from normative side by way of researching bibliography or secondary data consisting of primary law material, secondary law material and tertiary law material.The result of the research shows that the basic of nationalization action by the government underlying are due to economic inequality, where foreign capital companies start to dominate the main sectors in the national economy, and the other thing is the politics of nationalization law. Legal protection of investors is focused on preventive law protection, in which investors are given the opportunity to file an objection (inspraak) before a government decision in the definitive form of nationalization action.